Report of the International Capacity Building Training Program on Computable General Equilibrium (CGE) Modeling for Economic Policy Analysis - Nandi, Sukhendu; Barman, Subrata (CGIAR System Organization, 2024)
Many policy questions need to be addressed within an economy-wide framework that captures impacts on the overall economy, and at sector and household levels. Over the past 25 years, computable general equilibrium (CGE) models have become a standard tool for empirical economic analysis. CGE models are especially designed to evaluate the direct and indirect impacts of policies shocks at both macroeconomic and microeconomic scales. In recent years, improvements in model specification, data availability, and computer technology have improved the payoffs and reduced the costs of policy analysis based on CGE models, paving the way for their widespread use by policy analysts throughout the world. Given the demand for economy-wide analysis, the International Food Policy Research Institute (IFPRI) and the South Asian Network on Economic Modeling (SANEM), together with the Indian Council of Agricultural Research-Indian Agricultural Research Institute (ICAR-IARI) and Indian Council of Agricultural Research-National Institute of Agricultural Economics and Policy Research (ICAR-NIAP) organized an introductory training program on CGE modeling in New Delhi from April 29 to May 04, 2024. The course was aimed at researchers and policy analysts from South Asia who had some economics background but were interested in learning more about economy-wide models and their applications.